Antenatal Ultrasound Should Be For All; Congenital Diaphragmatic Hernia - A Case Report - Reyhan Julio Azwan; Vaulinne Basyir; Yusrawati yusrawati (Journal of Midwifery, 2021)
Congenital diaphragmatic hernia is an anatomical defect of the diaphragm, which allows protrusion of abdominal viscera into the chest, causing serious pulmonary and cardiac complications in the neonate. In this study we aimed to present a case of congenital diaphragmatic hernia. We investigated a 35-36 weeks of pregnancy, with a pregnancy carried out in a public hospital in Padang, West Sumatera. We suggest that if diagnosis occurs in the prenatal period, the prognosis of this disease improves.